Strategi Mitigasi Bencana Erupsi Gunung Semeru Di Kabupaten Lumajang - Pramitasari, Sintya; Septiana, Nazwa; Piliang, Dewi Arimbi Burhandani; Putri, Rayshya Chauliya Nadina; Bumbungan, Rafael Benino Ampangallo; Hadianto, Nuh Krama; Amin, M. Noer Falaq Al (Journal of Innovative and Creativity, 2026)
Mount Semeru is recorded as an active volcano with a high disaster potential for communities in Lumajang Regency. Therefore, disaster mitigation strategies are needed to reduce the risks and impacts of volcanic eruptions. This study aims to identify the implementation of both structural and non-structural mitigation in handling the eruption disaster of Mount Semeru in Lumajang Regency. The research uses a descriptive qualitative method through a literature study approach by collecting data from journals, government documents, regulations, and other scientific sources. The results show that structural mitigation efforts include the installation of an Early Warning System (EWS), monitoring CCTV, evacuation facilities, and disaster warning signs. Meanwhile, non-structural mitigation is carried out through disaster education and preparedness training for the community, as well as coordination with related agencies.